The Reflection of War and Occupation in The Novel (The Fall of Bora Qalla in The Old Story, Death of Maimun)'s Mardin Ibrahim - محمد علی, تاهر; عبدالقادر عارف, تانیا (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The novel is based on many different principles and genders, each of which has its own characteristics and is related to other genders. This research is an analysis description of both novels (The Citadel Pipe In a Kurdish Story and The Death of Monkeys) by Mardin Ibrahim, which reflects war and occupation on the side of the novelist messenger, who finds himself reflecting nature, animals, shonas, culture and Kurdish individuals.